Phytochemical analysis and potential natural compounds against SARS-CoV-2/COVID-19 in essential oils derived from medicinal plants originating from Lebanon. An information note. (4th July 2022) - Saab, Antoine M.; Tacchini, Massimo; Sacchetti, Gianni; Contini, Carlo; Schulz, Hartwig; Lampronti, Ilaria; Gambari, Roberto; Makhlouf, Hassane; Tannoury, Mona; Venditti, Alessandro; Bianco, Armandodoriano; Racagni, Giorgio
Abstract: The aim of the study is to identify potential natural compounds against SARS-CoV-2 occurring in essential oils (EOs) following literature data attesting their anti-viral activity. The epidemic virus that started in December 2019 in Wuhan, China, has spread worldwide as a global pandemic. The interest in the development of drugs from natural products has increased greatly in recent decades. (EOs) have been studied over the centuries and are known to possess various pharmaceutical properties. Recent antiviral and silico methods are used to discover phyto-compounds, suitable for coronavirus treatment. To obtain this result we employed gas chromatography for the analysis of essential oils from Laurus nobilis, Pinus pinea, Pistacia palaestina, Juniperus oxycedrus, Juniperus excelsa, Pinus brutia, Cupressus sempervirens, Lavandula stoechas, Origanum syriacum, O. ehrenbergi, Salvia tribola, Satureja thymbra, Calamintha origanifolia, Foeniculum vulgare, Mentha longifoli a, Cuminum cyminum and Pimpinella anisum .